IMPLEMENTATION OF EVIDENCE-BASED MEDICINE IN THE DIAGNOSIS AND PREVENTION OF CARDIOVASCULAR DISEASES - Rasulova Nilufar Farkhadovna (Modern American Journals, 2026)
Cardiovascular diseases remain the leading cause of morbidity and mortality worldwide, necessitating the application of scientifically validated approaches to improve diagnostic accuracy and preventive effectiveness. This study aims to analyze the implementation of evidence-based medicine in the diagnosis and prevention of cardiovascular diseases, with a focus on integrating high-quality clinical evidence into routine medical practice. The assessment is based on contemporary clinical guidelines, systematic reviews, and large-scale clinical trials evaluating diagnostic tools, risk stratification models, and preventive interventions for cardiovascular pathology. Particular attention is given to the role of evidence-based diagnostic algorithms, biomarker utilization, and non-invasive imaging techniques, as well as lifestyle and pharmacological prevention strategies supported by robust clinical outcomes. The findings indicate that the systematic application of evidence-based medicine enhances early detection of cardiovascular diseases, improves risk assessment, and significantly reduces the incidence of adverse cardiovascular events. The results underscore that embedding evidence-based principles into diagnostic and preventive strategies is essential for optimizing cardiovascular care and reducing the long-term burden of cardiovascular diseases.
Keywords: Cardiovascular diseases; evidence-based medicine; early diagnosis; disease prevention; clinical guidelines; risk stratification